2023
DOI: 10.1001/jama.2023.5997
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Cirrhosis and Its Complications

Abstract: ImportanceCirrhosis affects approximately 2.2 million adults in the US. From 2010 to 2021, the annual age-adjusted mortality of cirrhosis increased from 14.9 per 100 000 to 21.9 per 100 000 people.ObservationsThe most common causes of cirrhosis in the US, which can overlap, include alcohol use disorder (approximately 45% of all cases of cirrhosis), nonalcoholic fatty liver disease (26%), and hepatitis C (41%). Patients with cirrhosis experience symptoms including muscle cramps (approximately 64% prevalence), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 124 publications
2
42
0
Order By: Relevance
“…For example, lactulose therapy improves sleep for patients with covert hepatic encephalopathy . Following the publication of our Review, we showed that many patients with cirrhosis experienced improved sleep with use of lactulose even if they had not been diagnosed with hepatic encephalopathy …”
mentioning
confidence: 82%
See 2 more Smart Citations
“…For example, lactulose therapy improves sleep for patients with covert hepatic encephalopathy . Following the publication of our Review, we showed that many patients with cirrhosis experienced improved sleep with use of lactulose even if they had not been diagnosed with hepatic encephalopathy …”
mentioning
confidence: 82%
“…In Reply Dr Braillon makes multiple important points about the recommendation of using hydroxyzine for sleep in patients with cirrhosis. Our Review focused on evidence-based therapies for patients with cirrhosis, and unfortunately, to date, trials of specific nonpharmacologic therapies for sleep disorders in the context of cirrhosis are lacking. However, in a recent article about contemporary management of pain in cirrhosis, we recommended nonpharmacologic interventions for sleep disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We plan to cover a broad range of topics relevant to internal medicine, such as substance use disorders, obesity, and dementia. These reviews will follow a format similar to that of other JAMA Network journals; for example, a recently published review on the management of cirrhosis and another on treatment strategies for symptoms of menopause …”
mentioning
confidence: 99%
“…To the Editor I believe that the recent Review about the diagnosis and management of cirrhosis wrongly promoted off-label use of hydroxyzine in its abstract by mentioning “[t]rials addressing symptoms of cirrhosis have demonstrated efficacy for hydroxyzine in improving sleep dysfunction….”…”
mentioning
confidence: 99%